Managing Transaction Costs in International Production; Evidence on Entrepreneurship from Case Studies in The Netherlands - Ebel Berghuis; Frank A.G. den Butter (Tinbergen Institute, 2013)
This era of globalisation is characterized by an ongoing international fragmentation of production where the supply chain is split up in more and more parts. The traditional Ricardian theory of trade in products governed by comparative advantages is replaced by a modern theory of trade in tasks. This trend requires new entrepreneurial skills in the organisation of production. Tasks are outsourced to those places in the world where the lower production costs outweigh the additional transaction costs associated with the fragmentation of production. This managing of transaction costs, which we label transaction management, has become a major entrepreneurial skill in transaction economies like the Netherlands. It is determinant for the make or buy and location decisions. This paper investigates the practice of transaction management by using data from in-depth interviews with seven companies in the Netherlands which are actually engaged in this modern way of org anising production. It shows that the various ways of coping with transaction costs in the organisation of production play an important role in the strategic decision making of the internationally operating entrepreneurs. However, transaction costs are only intuitively dealt with in organising production. Therefore it seems that support from more formal argumentation, based on the theories of transaction cost economics and new institutional economics, is warranted.
Keywords: F14; L23; L24; M11; M16; 330; Fragmentation of production; outsourcing; managing transaction costs; new institutional economics